Effectiveness of Lavender Aroma Therapy on Post-Sectio Caesarea Pain Intensity in the Obstetric Room Bhayangkara Padang Hospital - Pebrina, Melia; Khairani, Septi; Fernando, Fenny; Fransisca, Dewi; Darma, Ika Yulia; Hayu, Ramah (PT. Riset Press International, 2023)
Sectio caesarea delivery has an impact on a higher level of pain in the operated abdomen compared to normal delivery. One therapy that can be given is lavender aromatherapy. This aromatherapy contains ingredients that can increase alpha waves in the brain, thus making the mother feel relaxed. The purpose of the study was to see the effectiveness of giving lavender aromatherapy to the intensity of post sectio caesarea pain in the Midwifery Room of Bhayangkara Hospital Padang in 2022. This type of research is a quasi-experimental study with a One-Group Pre-Test-Post- Test approach which was carried out from June-August 2022. The population of all post sectio caesarea mothers was 57 people with a purposive sampling technique of 16 people. Collecting data using observation sheets. The data were computerized with univariate and bivariate analysis using the Wilcoxon test with a significance level of = 0.05. The results obtained that the average post sectio caesarea pain before being given lavender aromatherapy was 5.63 and reduced after being given lavender aromatherapy was 3.38. The results of the bivariate analysis showed the effectiveness of giving lavender aromatherapy to the intensity of post sectio caesarea pain (p = 0.000) The results of the study concluded that there was an effectiveness of giving lavender aromatherapy to the intensity of post sectio caesarea pain, it is hoped that nurses would apply lavender aromatherapy for caesarean post section patients as an alternative in pain management and apply other therapies as companion therapy to reduce postoperative pain intensity.